Pengaruh Naupli Artemia yang Diperkaya dengan N-3 HUFA terhadap "Budget" Energi Larva Ikan Red Sea Bream Pagrus major - O. Sumule (Jurnal Akuakultur Indonesia)
Energy budget of red sea bream Pagrus major larvae fed n-3 highly unsaturated fatty acids (HUFA)-enriched (EA) and non-enriched (NEA) Artemia nauplii was constructed as: EI = F + M + U + G, where EI is energy intake, F energy loss as feces, M energy loss for metabolism, U energy loss as non-fecal matter based on ammonia excretion, and G energy for growth. Larvae (29 days post hatching, 41,1 mg mean wet weight) were reared in six 80 1 circular tanks and fed EA and NEA for 12 days, with three replicates for each type of food. Overall, growth of larvae was significantly higher in EA group than NEA group. Oxygen consumption, as heat increment, was also significantly higher in EA-fed larvae than NEA-fed larvae. The energy budget of a 100-mg larva was partitioned into: 100% of EI = 38,4% for G + 34,5% for M + 2,9% for U + 24,2% for F, for EA group, whereas 100% of EI = 29,1% for G + 30,1% for M + 3,3% for U + 37.4% for F, for NEA group. Assimilation, gross conversion, and net conversion efficiencies were higher in EA-fed larvae than NEA-fed larvae, which were attributed to the higher energies channeled to metabolism and growth in the former. This study concluded that HUFA enrichment of Artemia nauplii increased energy absorption but reduced energy excretion in red sea bream larvae. Key words : Pagrus major, larvae. HUFA enriched Artemia nauplii, oxygen consumption, ammonia excretion, heat increment, energy budget